Optimal Fiscal Policy with Private and Public Investment in Education - Luigi Marattin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
This paper develops a three periods OLG growth model where agents accumulate human capital in the first period (benefiting from grandfathers savings, public expenditure in education, and human capital level of their parents), work and save in the second period (earning a salary proportional to the human capital level accumulated), and retire in the thid period, leaving bequest on for the young generation. Government raises taxes on labour and capital in order to finance public expenditure in education. We derive conditions for equilibrium and for the rate of growth, and then carry out welfare analysis in order to determine optimal taxation in a Nash policy setting.
Keywords: 330